Pekanbaru City Regional Regulation No. 2 of 2023 on the Protection of Women and Children from the Perspective of Islamic Family Law - Fauzi, Ahmad; Nelli, Jumni; Johari, Johari; Kori, Hendri; Zikri, Ahmad; Rahman, Rahman (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to explain Pekanbaru City Regional Regulation No. 2 of 2023 regarding the Protection of Women and Children in order to provide protection and prevent violence against women and children within Islamic families. Islam views women and children as gifts from Almighty God, who must be protected as they possess inherent dignity, honor, and rights as human beings that must be upheld. The protection of women and children from acts of violence is intended to guarantee and protect their rights so that they can live in peace, grow and develop, and participate optimally according to human dignity and worth. This research is a library study and is also confirmed through field data using a qualitative approach and juridical sociological analysis techniques. The primary source of data is the Regional Regulation (Perda), while secondary materials include books related to Islamic Family Law. Tertiary legal materials consist of legal norms, Arabic and English dictionaries, and documents deemed important to this research. The findings show that the existence of Pekanbaru City Regional Regulation No. 2 of 2023 is a response to several issues of domestic violence experienced by women and children in households, viewed from philosophical, sociological, and juridical foundations